ISOLASI DAN IDENTIFIKASI BAKTERI TERMOFILIK PENGHASIL AMILASE DARI SUMBER AIR PANAS SIDEBUK-DEBUK SUMATERA UTARA - Nin Suharti Suharti; Geminsah Putra (Poltekkes Kemenkes Medan, 2022)
Hot springs or hot springs are springs that are produced as a result of the release of groundwater from the earth's crust after experiencing geothermal heating. Indonesia is one of the most active tectonic regions in the world with more than 70 active volcanoes, and has many geothermal areas. Hot springs are a suitable growth medium for thermophilic bacteria. Thermophilic bacteria are a group of bacteria that adapt to high-temperature environmental conditions, with temperatures ranging from 50°C-75°C. The natural habitat of thermophilic bacteria is widespread throughout the earth's surface, including in hot springs, volcanic craters or volcanic areas. One of the hot springs in North Sumatra province is sidebuk-debuk, which is located in Bandar Baru sub-district. is a hot spring, which has a temperature between 50°C – 75°C. At this time thermophilic bacteria are studied and researched intensively for reasons of developing basic research and biotechnology applications. Thermophilic bacteria have the potential to produce heat-resistant/ thermostable enzymes and can be used in industry, waste treatment processes and mineral weathering. Amylase is an important enzyme that is widely used in industrial applications through synthesis reactions and hydrolysis reactions, accounting for almost 65% of the total sales of enzymes in the world. Researchers are interested in knowing more about the role of thermostable enzymes in modern biotechnology today, therefore it is necessary to conduct research aimed at isolating and identifying local isolates of thermophilic bacteria as potential sources of enzymes, especially in North Sumatra. From this study, 19 isolates of Bacillus sp bacteria were obtained from Sidebuk-debuk hot springs based on phenotypic characters by looking at macroscopic, microscopic and biochemical characteristics, with 9 isolates of thermophilic bacteria that have the potential to produce amylase as indicated by the presence of a clear zone around the bacterial colonies.Keywords: Hot Springs, Bacillus sp Bacteria,